Tinnitus Management in Lateral Skull Base Lesions - Juan, Juan San; Basura, Gregory J. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Tinnitus, the phantom perception of sound in the absence of a physical sound source, is a complex problem with multiple etiologies. While most commonly presenting in a subjective fashion caused by measurable hearing loss, other etiologies including lateral skull base tumors that encroach on middle and inner ear structures can lead to phantom sound perception as well. In addition to discussing the basic background of tinnitus, here we also review current theories of etiology that include central auditory and nonauditory neural mechanisms and potential treatments that range from sound therapy to medications to cognitive and behavioral therapies and cranial nerve and brain stimulation. One main purpose of this article is to relate tinnitus causes to skull base tumors, surgical removal, and resultant sequelae, including damage to cranial nerves resulting in audiovestibular dysfunction. We also discuss the utility of microvascular decompression for both tumor and nontumor-associated tinnitus and the current literature regarding hearing preservation rates and tinnitus perception, where documented, with the three common treatment modalities employed for most lateral skull base tumors that includes watchful waiting with serial imaging, stereotactic radiosurgery and primary surgical resection using hearing preservation and hearing ablative approaches. The management of skull base tumors is a complex process that depending upon the approach and sequelae, may lead to manageable or worsening phantom sound perception that must be considered when discussing the multiple treatment options with patients.
Keywords: hearing loss; meningioma; skull base surgery; stereotactic radiosurgery; tinnitus; vestibular schwannoma